2021
DOI: 10.1186/s13018-021-02262-3
|View full text |Cite
|
Sign up to set email alerts
|

Co-treatment with disulfiram and glycyrrhizic acid suppresses the inflammatory response of chondrocytes

Abstract: Background Osteoarthritis (OA) is a kind of systemic musculoskeletal disorder and a most important factor for causing disability and physical painfulness. Nevertheless, due to the fact that OA can be triggered by multiple etiological factors, this disease is hard to be cured. Therefore, it is of great necessity for us to find novel targets or drugs for OA treatment. Materials and methods The chondrocytes were treated with lipopolysaccharide (LPS) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Co-treatment with disulfiram and glycyrrhizic acid promote the proliferation and alleviate pyroptosis in LPS and ATP stimulated C28/I2 chondrocytes, and can reduce the production of ROS. DSF, when used at high concentrations, shows little effect on cell proliferation and pyroptosis (Li et al, 2021). This may provide new ideas for the treatment of osteoarthritis.…”
Section: Disulfiram For the Inflammatory Response Of Chondrocytesmentioning
confidence: 94%
See 1 more Smart Citation
“…Co-treatment with disulfiram and glycyrrhizic acid promote the proliferation and alleviate pyroptosis in LPS and ATP stimulated C28/I2 chondrocytes, and can reduce the production of ROS. DSF, when used at high concentrations, shows little effect on cell proliferation and pyroptosis (Li et al, 2021). This may provide new ideas for the treatment of osteoarthritis.…”
Section: Disulfiram For the Inflammatory Response Of Chondrocytesmentioning
confidence: 94%
“…Degenerative changes in articular cartilage can result in osteoarthritis (Goldring and Berenbaum, 2015). In C28/I2 cells (human chondrocytes), LPS and ATP can induce inflammation and pyroptosis (Li et al, 2021). Co-treatment with disulfiram and glycyrrhizic acid promote the proliferation and alleviate pyroptosis in LPS and ATP stimulated C28/I2 chondrocytes, and can reduce the production of ROS.…”
Section: Disulfiram For the Inflammatory Response Of Chondrocytesmentioning
confidence: 99%
“…Targeting pyroptosis in OA has been proposed in in vitro experimental studies, where chondrocytes were activated by LPS and ATP, and treatment with disulfiram and glycyrrhizin acid resulted in suppression of the inflammatory response and reduction of pyroptosis. 102 Another interesting finding was that treatment with Icariin also suppressed GSDMD expression, and chondrocyte pyroptosis, and protected against cartilage degeneration in the MIA rat OA model. 54 Other molecules; for instance, morroniside and loganin were assessed in a mouse model of OA, and the authors found that those two iridoid glycosides extracted from Cornus officinalis were protective against cartilage degradation by reducing chondrocyte pyroptosis via inhibition of NF-κB signaling.…”
Section: Other Potential Future Directions For Inflammasome Targeting...mentioning
confidence: 95%
“…Preclinical studies have demonstrated that icariin [ 128 ], loganin [ 129 ], licochalcone Am [ 130 ], irisin [ 131 ], quercetin [ 126 ], morroniside [ 132 ], and rapamycin [ 133 ] inhibit the classical pyroptotic pathway and reduce chondrocyte death, suggesting future roles in the treatment of OA. In addition, combined treatment with antagonists of GSDMD (disulfiram) and HMGB1 (glycyrrhizic acid) can attenuate chondrocyte pyroptosis, inhibit inflammation, and promote chondrocyte proliferation in vitro, thereby suggesting a therapeutic approach for OA [ 134 ]. In summary, pyroptosis is a well-defined pathogenic mechanism of OA.…”
Section: Pyroptosis and Degenerative Diseases Of The Elderlymentioning
confidence: 99%